Hubungan Kondisi Lingkungan Dan Perilaku Masyarakat Dengan Kejadian Filariasis Di Desa Muaro Putuih Wilayah Kerja Puskesmas Tiku Kabupaten Agam: The Relationship between Environmental Conditions and Community Behavior with the Incidence of Filariasis In Muaro Putuih Village, Tiku Health Center Working Area, Agam Regency - Weni Sartiwi (Fakultas Keperawatan Universitas Andalas, 2018)
Filariasis is a systemic infection caused by filarial worms that live in the human lymph nodes and blood. The most important thing to do is to decrease the filariasis incidence that influenced by environmental condition and behavior. The purpose of this research was to know relationship between environmental condition and people behavior with filariasis incidence at muaro putuih village tiku public health centre working area agam district. Type of this research was descriptive analitik research with cross sectional design. The population of this research was all head of family at muaro putuih village tiku public health centre working area agam number 100 head of family with 50 head of family samples. Taking samples in this research was using simple random sampling. This research was done on February 10 until March 2, 2016. The data was collected using a questionnaire. Data processing techniques were editing, coding, entry and cleaning. Univariate analysis was analyzed using chi-square test shown in cross table form. The results showed that from 50 respondents, more than half of respondents (54%) had environmental at risk, more than half of respondents (54%) had bad behavior, more than half of respondents (58%) not suffering from filariasis. There was relationship between environmental condition and filariasis incidence (p = 0.000), there was relationship between behavior and filariasis incidence (p = 1.000), there was a relationship between medication adherence and recovery (p=0.017) at muaro putuih village tiku public health centre working area agam district. It is expected for public health centre in order to give health education about the filariasis disease.